Monkey and Elephant go gadding - Schaefer, Carole Lexa; Bernstein, Galia (Somerville, Massachusetts Candlewick Press, 2014)
Monkey and Elephant are very good friends, very good friends who look too nice to just stay at home. So they decide to go gadding. "Gadding?" said Elephant. "What's that?" "Gadding," said Monkey, "is walking along, looking around, finding something fun, stopping awhile, then moving on." Along the way, Monkey and Elephant meet up with some old friends, and three new ones, too. You never know what fun surprises you'll discover when you decide to go gadding!
Keywords: Elephants -- Juvenile fiction; Friendship -- Juvenile fiction; Monkeys -- Juvenile fiction; Elephants -- Fiction; Friendship -- Fiction; Monkeys -- Fiction; Children's stories